Penerapan Infrastruktur Wisata Berkelanjutan Melalui Penerapan Konsep Struktur Tahan Gempa - Nurul Rochmah Pramadika; Try Kurniawan Akhbar; Sarmoko Saridi (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia, situated within the Pacific Ring of Fire, faces a high susceptibility to seismic activity. This geographical vulnerability presents significant challenges for the tourism sector, especially concerning supporting infrastructure such as hotels, resorts, tourist bridges, and public facilities. Tourist safety is not only a primary concern but also a critical element in achieving sustainable tourism development. This study explores the application of earthquake-resistant structural concepts in tourism infrastructure construction, emphasizing technical planning aspects and their relevance to destination sustainability. The methodology includes a literature review of earthquake-resistant building standards (SNI 1726:2019 and international regulations), case study analysis of tourism areas vulnerable to earthquakes in Indonesia, and an evaluation of the integration of civil engineering principles with sustainable tourism development. The findings indicate that implementing earthquake-resilient engineering not only enhances safety but also supports long-term cost efficiency, environmental protection, and improved tourist comfort. Therefore, developing earthquake-resistant tourism infrastructure is a vital strategy for maintaining Indonesia’s competitiveness in the global tourism market